2007
DOI: 10.1016/j.jmaa.2006.09.061
|View full text |Cite
|
Sign up to set email alerts
|

A SIRS epidemic model with infection-age dependence

Abstract: Based on J. Mena-Lorca and H.W. Hethcote's epidemic model, a SIRS epidemic model with infectionage-dependent infectivity and general nonlinear contact rate is formulated. Under general conditions, the unique existence of its global positive solutions is obtained. Moreover, under more general assumptions than the existing, the existence and asymptotical stability of its equilibria are discussed. In the end, the condition on the stability of endemic equilibrium is verified by a special model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…While the general model from [13] was largely neglected until rather recently, most of the literature concentrating on the particular case of constant rates, there has been since the 1970s some papers considering age dependent epidemic models, see in particular [9]. More recently, several papers have introduced coupled PDE/ODE models for studying age of infection dependent both infectivity and recovery rate, see in particular [23,11,24,17,5] and chapter 13 in [18]. Since the beginning of the Covid-19 pandemic, a huge number of papers have been produced, with various models of the propagation of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…While the general model from [13] was largely neglected until rather recently, most of the literature concentrating on the particular case of constant rates, there has been since the 1970s some papers considering age dependent epidemic models, see in particular [9]. More recently, several papers have introduced coupled PDE/ODE models for studying age of infection dependent both infectivity and recovery rate, see in particular [23,11,24,17,5] and chapter 13 in [18]. Since the beginning of the Covid-19 pandemic, a huge number of papers have been produced, with various models of the propagation of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Many mathematical models on this topic have been studied [12][13][14][15][16][17]. Reference [17] states that, in infinite scale-free networks, epidemic processes do not possess an epidemic threshold below which diseases cannot produce a major epidemic outbreak or the inset of an endemic state.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last three decades, the infection-agedependent epidemic models have been studied extensively and a number of mathematical models have been proposed to address different aspects related to age in epidemic transmission. Mathematical issues such as existence of steady state solutions as well as stability property have been analysis [14][15][16][17][18][19][20]. An excellent review regarding the epidemic modelling and age-structured epidemic modelling can be found in [21].…”
Section: Introductionmentioning
confidence: 99%